The Results of Hemivertebra Resection by the Posterior Approach in Children with a Mean Follow-Up of Five Years - Ramazan Erden Erturer; Bekir Eray Kilinc; Bahadir Gokcen; Sinan Erdogan; Kursat Kara; Cagatay Ozturk (Advances in Orthopedics)
Aim. To evaluate the radiologic and clinical results of patients who underwent deformity correction and stabilization for congenital spinal deformities using pedicle screws after hemivertebra resection. Material and Method. Nine patients, mean age 9.2, who underwent posterior hemivertebrectomy and transpedicular fixation for congenital spinal deformity and had longer than five years of follow-up were evaluated retrospectively. The hemivertebrae were located in the thoracic region in 4 patients and thoracolumbar transition region in 5 patients. The patients were evaluated radiologically and clinically in the postoperative period. Results. Mean length of follow-up was 64.2 months. The mean operating time was 292 minutes. The mean blood loss was 236 mL. The average hospitalization time was 7 days. The amount of correction on the coronal planes was measured as 31%. The mean segmental kyphosis angle was 45.7 degrees preoperatively and it was measured 2.7 degrees in the follow-up period. There were no statistically significant differences between the early postoperative period and final follow-up X-rays with respect to coronal and sagittal plane deformities. Conclusion. The ability to obtain a sufficient and balanced correction in the cases accompanied by long compensator curvatures that have a structural character in hemivertebra may require longer fusion levels.